The Effect of Breastfeeding Duration and Parental Attitudes on Academic Success - Kılıç, Mahmut; Ozan, Tuğba Uçak (International Journal of Child Health and Nutrition, 2022)
This study aims to reveal the relationship between the academic success of the students and the duration of breastfeeding, parental attitude, and other variables. This cross-sectional study was conducted among 9th-grade high school students in 2019. A total of 501 students and their families participated in the research. Academic success in order of importance in multivariable linear regression analysis, the increase in the education level of the father, the preparation for the exam, the increase in the protective and democratic parental attitude, the shortening of the first walking age, and the increase in the maternal age increase the high school exam score. Breastfeeding duration and authoritarian parental attitudes were not found to be statistically significant. The protective and democratic attitude of the parents, the high level of father education, and early walking positively affect academic success, while the breastfeeding duration is insignificant.